Assessment of Selected Alternative Fuels for Spanish Navy Ships According to Multi-Criteria Decision Analysis - Rocio Maceiras; Victor Alfonsin; Miguel A. Alvarez-Feijoo; Lara Llopis (Journal of Marine Science and Engineering, 2023)
Climate change and environmental degradation are growing concerns in today’s society, which has led to greater awareness and responsibility regarding the need to adopt sustainable practices. The European Union has established the goal of achieving climate neutrality by 2050, which implies a significant reduction in greenhouse gas emissions in all sectors. To achieve this goal, renewable energies, the circular economy, and energy efficiency are being promoted. A major source of emissions is the use of fossil fuels in different types of ships (from transport ships to those used by national navies). Among these, it highlights the growing interest of the defense sector in trying to reduce these emissions. The Spanish Ministry of Defense is also involved in this effort and is taking steps to reduce the carbon footprint in military operations and improve sustainability in equipment acquisition and maintenance. The objective of this study is to identify the most promising alternative fuel among those under development for possible implementation on Spanish Navy ships in order to reduce greenhouse gas emissions and improve its capabilities. To achieve this, a multi-criteria decision-making method will be used to determine the most viable fuel option. The data provided by the officers of the Spanish Navy is of great importance, thanks to their long careers in front of the ships. The analysis revealed that hydrogen was the most suitable fuel with the highest priority, ahead of LNG, and scored the highest in most of the sections of the officials’ ratings. These fuels are less polluting and would allow a significant reduction in emissions during the navigation of ships. However, a further study would also have to be carried out on the costs of adapting to their use and the safety of their use.